STRATEGI ORANG TUA DALAM PENERAPAN POLA HIDUP SEHAT PADA ANAK USIA 5-6 TAHUN DI TK ABA V MEDAN - Khairunnisa Wibisono; Gita Noveri Eza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted to explore the strategies parents use to instill healthy lifestyle habits in children aged 5–6 years, focusing on the aspects of habit formation, modeling, guidance, and home environment management in fostering healthy lifestyles among children at ABA V Kindergarten in Medan. This study employed a qualitative approach with a phenomenological design. The method used was interviews with a descriptive technique. Based on the results of the study, it was found that the strategies employed by individual parents vary significantly and are not limited solely to the aspects of habit formation, modeling, guidance, and environmental regulation. Each parent within the family has their own unique strategy. Some parents consistently promote a healthy lifestyle through daily healthy habits practiced together with the parents serving as role models for their children. Others strive to establish healthy living habits by providing a nutritionally balanced diet and physical activities that are expected to support their children’s current growth and development. There are also parents who do not strictly enforce discipline to compel their children to maintain healthy habits; instead, they encourage children through a relaxed approach while still providing guidance and striving to offer the necessary resources for their children.